National Partnership for Maternal Safety: Consensus Bundle on Obstetric Care for Women With Opioid Use Disorder. Issue 2 (August 2019) - Krans, Elizabeth E.; Campopiano, Melinda; Cleveland, Lisa M.; Goodman, Daisy; Kilday, Deborah; Kendig, Susan; Leffert, Lisa R.; Main, Elliott K.; Mitchell, Kathleen T.; O'Gurek, David T.; D'Oria, Robyn; McDaniel, Deidre; et al.
Abstract : The opioid epidemic is a public health crisis, and pregnancy-associated morbidity and mortality due to substance use highlights the need to prioritize substance use as a major patient safety issue. To assist health care providers with this process and mitigate the effect of substance use on maternal and fetal safety, the National Partnership for Maternal Safety within the Council on Patient Safety in Women's Health Care has created a patient safety bundle to reduce adverse maternal and neonatal health outcomes associated with substance use. The Consensus Bundle on Obstetric Care for Women with Opioid Use Disorder provides a series of evidence-based recommendations to standardize and improve the quality of health care services for pregnant and postpartum women with opioid use disorder, which should be implemented in every maternity care setting. A series of implementation resources have been created to help providers, hospitals, and health systems translate guidelines into clinical practice, and multiple state-level Perinatal Quality Collaboratives are developing quality improvement initiatives to facilitate the bundle-adoption process. Structure, process, and outcome metrics have also been developed to monitor the adoption of evidence-based practices and ensure consistency in clinical care. Abstract : This bundle provides evidence-based recommendations to improve the quality of care for pregnant women with opioid use disorder.